Circulating Cell-Free DNA Yield and Circulating-Tumor DNA Quantity from Liquid Biopsies of 12 139 Cancer Patients. (1st November 2021) - Huang, Richard S P; Xiao, Jinpeng; Pavlick, Dean C; Guo, Cui; Yang, Lei; Jin, Dexter X; Fendler, Bernard; Severson, Eric; Killian, Jonathan Keith; Hiemenz, Matthew; Duncan, Daniel; Lin, Douglas I; et al.
Abstract: Background: The amounts of circulating cell-free DNA (cfDNA) and circulating-tumor DNA (ctDNA) present in peripheral blood liquid biopsies can vary due to preanalytic/analytic variables. In this study, we examined the impact of patient age, sex, stage, and tumor type on cfDNA yield, ctDNA fraction, and estimated ctDNA quantity from a large cohort of clinical liquid biopsy samples. Methods: We performed a retrospective analysis of 12   139 consecutive samples received for liquid biopsy (FoundationOne ® Liquid) clinical testing. Results: Significant differences in both cfDNA yield and estimated ctDNA quantity were observed based on the underlying tumor type that initiated the liquid biopsy analysis and the stage of the patient ( P  <   0.001). In addition, significant differences in ctDNA quantity were present based in both the patient age and sex ( P  <   0.001). Importantly, we saw a significantly higher success rate of issuing a clinically useful report in patients with higher levels of cfDNA yield and ctDNA quantity ( P  <   0.001). Conclusions: In this study, we show that ctDNA quantity varied significantly based on patient age, sex, stage, and tumor type, which could offer an explanation as to why certain liquid biopsy specimens are more likely to fail sequencing or provide clinically meaningful results. In addition, this could affect future clinical decisions on the blood sample volumes required to allow successful liquid biopsy testing.